Analisis keungan keluarga lansia pensiun - Hestiningrum, Sistia Edi Anisa Dwi (Institute for Advanced Science Social, and Sustainable Future, 2023)
The purpose of this study was to analyze the effect of financial literacy, financial planning for the elderly and real estate on family financial well-being at retirement age. The example in this study is 120 families whose husbands or wives have reached retirement age (55-65 years). Respondents were selected through purposive sampling, as many as 60 respondents from each rural area. The study was conducted in Weleri District as a sub-district area and Montongsari Village as a rural area. Data were analyzed using descriptive analysis, independent sample test and multiple linear regression tests. The results showed that there were significant differences in education level, employment status and average income between urban and rural respondents, with urban respondents achieving a higher median score. in rural areas. The average level of financial literacy and financial well-being in rural areas.